PC6 acupoint stimulation for the prevention of postcardiac surgery nausea and vomiting: a protocol for a two-group, parallel, superiority randomised clinical trial. Issue 11 (13th November 2014) - Cooke, Marie; Rickard, Claire; Rapchuk, Ivan; Shekar, Kiran; Marshall, Andrea P; Comans, Tracy; Doi, Suhail; McDonald, John; Spooner, Amy
Abstract : Introduction: Postoperative nausea and vomiting (PONV) are frequent but unwanted complications for patients following anaesthesia and cardiac surgery, affecting at least a third of patients, despite pharmacological treatment. The primary aim of the proposed research is to test the efficacy of PC6 acupoint stimulation versus placebo for reducing PONV in cardiac surgery patients. In conjunction with this we aim to develop an understanding of intervention fidelity and factors that support, or impede, the use of PC6 acupoint stimulation, a knowledge translation approach. Methods and analysis: 712 postcardiac surgery participants will be recruited to take part in a two-group, parallel, superiority, randomised controlled trial. Participants will be randomised to receive a wrist band on each wrist providing acupressure to PC six using acupoint stimulation or a placebo. Randomisation will be computer generated, use randomly varied block sizes, and be concealed prior to the enrolment of each patient. The wristbands will remain in place for 36 h. PONV will be evaluated by the assessment of both nausea and vomiting, use of rescue antiemetics, quality of recovery and cost. Patient satisfaction with PONV care will be measured and clinical staff interviewed about the clinical use, feasibility, acceptability and challenges of using acupressure wristbands for PONV. Ethics and dissemination: Ethics approval will be sought from appropriate Human Research Ethics Committee/s before start of the study. A systematic review of the use of wrist acupressure for PC6 acupoint stimulation reported minor side effects only. Study progress will be reviewed by a Data Safety Monitoring Committee (DSMC) for nausea and vomiting outcomes at n=350. Dissemination of results will include conference presentations at national and international scientific meetings and publications in peer-reviewed journals. Study participants will receive a one-page lay-summary of results. Trial registration number: Australian New Zealand Clinical Trials Registry—ACTRN12614000589684.